(untitled) (Bioscience Journal, 2017)
To gain knowledge into the social, emotional and sexual implications experienced by women attending the Ostomy Program in the municipality of Jataí-GO. This is a descriptive, exploratory and qualitative approach. The research was conducted in a basic care service, between May and September 2016. Eleven women were interviewed, using a semi-structured questionnaire and an audio recorder. The implications lived by these women in the social, emotional and sexual domains were evident. Through the accounts provided, it was possible to perceive sadness, fear and nonconformity in coming to terms with their new reality. The suffering reported by some patients was visible and from such, they need arose for the creation and implantation of a support group, in which it was possible for these women to exchange experiences.